Critical Analysis of War through Robert Graves’s Good-Bye to All That and Julian Barnes’s Staring at the Sun - Olivier, ABODOHOUI Orerien (Journal of Ecohumanism, 2025)
Good-Bye to All That and Staring at the Sun are commonly known as ones of the famous post-war novels that pinpoint the disastrous and indelible events that affect the peaceful atmosphere during world wars. Even though, it is the fruit of Barnes and Robert’s imagination, these novels shed light on the consequences of World War I and World War II, starting from wounds, loss of lives to the destruction of social environment and public places. Both Robert Graves and Julian Barnes use different narrative styles to relate the facts. While Robert prefers a direct account of events, Barnes’s Staring at the Sun is a more complex novel that requires readers’ imaginative skills to better understand some facts that have been extremely reshaped by the narrator. Anyway, one could easily understand that Barnes has made an in-depth account of the World War II, giving more details about dates of attacks. From the first novel to the second, it is obvious that the period of world war I and World War II are the saddest period characterised by unending bomb attacks and lack of peace in the whole world. Life and death become close friends so that one’s destiny may change in a couple of minutes. To achieve my goal, qualitative method has been applied with a special glance at Good-Bye to All That by Robert Grave and Julian Barnes’s Staring at the Sun. Thus, reading these works through the lenses of new historicism and structuralism help to penetrate the two authors’ fictional world. The results show that war leads to an uncountable number of deaths, destroys social atmosphere and creates economic crisis.